Aerosol-generating procedures in head and neck surgery – can we improve practice after COVID-19?. Issue 6 (July 2020) - Kerawala, C.; Riva, F.
Abstract: The COVID-19 pandemic has had a dramatic impact on international medicine practice. The propensity for head and neck surgery to generate aerosols needs special consideration over and above simply adopting personal protective equipment. This study sought to interrogate the literature and evaluate whether which additional measures might provide benefit if routinely adopted in minimising viral transmission.